LITERATURE REVIEW: ANTIDIABETIC ACTIVITY OF HONEY - MAHANI; NURFAUZIYAH, SHASKI GHINA; WULANDARI, ENDAH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of this study is to determine the antidiabetic activity of honey for people with Type 2 diabetes mellitus (T2DM) by looking at its effect on glycemic response, glycemic control, and its synergistic combination with antidiabetic drugs. Methods: The literature review starts from problem identification, data collecting, sorting the obtained data, reading, and analyzing, finally, compiling it into a systematic review. Results: The results show that honey has antidiabetic potential for people with T2DM as indicated by resulting good glycemic response and its combination with antidiabetic drugs results in positive glycemic control. Conclusion: Honey possesses antidiabetic activity that could make it as an ideal supplementation for people with T2DM by helping them to achieve the ideal glycemic control and avoid further diabetic complications.